The Politics of Immigration (2nd Edition) : Questions and Answers - Guskin, Jane; Wilson, David L. (David Leigh), 1946- (Book collections on Project MUSE., 2017)
"A straightforward discussion of the issues surrounding immigration U.S. immigration has been the subject of furious debates for decades. On one side, politicians and the media talk about aliens and criminals, with calls to 'deport them all.' On the other side, some advocates idealize immigrants and gloss over problems associated with immigration. Dialogue becomes possible when we dig deeper and ask tough questions: Why are people in other countries leaving their homes and coming here? What does it mean to be 'illegal'? How do immigration raids, prisons, and border walls impact communities? Who suffers and who profits from our current system--and what would happen if we transformed it? The Politics of Immigration: Questions and Answers goes beyond soundbites to tackle these concerns in straightforward language and an accessible question-and-answer format. First published in 2007, this updated and expanded edition is an effective tool to confront current stereotypes and disinformation. Those who believe immigrants take jobs from citizens, don't pay taxes, strain public services, and threaten the dominant culture will find their assumptions challenged with compelling arguments and hard data. Ideal for classroom use, The Politics of Immigration provides those who are undecided about immigration with the facts and clear reasoning they need to develop an informed opinion"--Provided by publisher.